(untitled) (Medical Forum Monthly, 2024)
Objective: Examination of the relation of age and hypertension duration on relationship between hypertension with dyspnea. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Department of Anatomy and Medicine Shahida Islam Medical Complex, Lodhran January 2018 to July 2018. Materials and Methods: A cross-sectional study was conducted in the outpatient division after taking ethical approval from Shahida Islam Medical Complex, Lodhran. The inclusion criteria of the study were 18 years or above age, either gender, having history of hypertension which was self-reported or intake of anti-hypertensive medication. After analyzing the capability and obtaining oral informed consent, all the demographic statistics and hypertension related clinical signs and symptoms were recorded through interview by using a structured questionnaire whereas the blood pressure levels were measured by a sphygmomanometer with stethoscope. Chi-square test was used for inferential analysis whereas the significant level was placed at 0.05. Results: The study results showed that overall dyspnea was not notably related with systolic and diastolic hypertension but among patients aged up to 35 years it was notably related with diastolic hypertension (p=0.016) while among patients aged 56 years or above it was markedly related with systolic hypertension (p=0.016). Moreover, among patients with 10 years or more duration of hypertension it was remarkably related with systolic hypertension (p=0.037). Conclusion: According to the study findings it is established that both age and hypertension duration modify the relationship between hypertension and dyspnea. While deciding the management plan for hypertensive patients, the role of their age and hypertension duration should not be ignored.